Waging Modern War : Bosnia, Kosovo, and the Future of Combat - Clark, Wesley K., Gen. (New York Public Affairs, 2002)
This is a paperbound reprint of a 2001 book. The man in charge of the bombing of Yugoslavia during the war in Kosovo proudly recounts his exploits as the NATO Supreme Allied Commander for Europe and offers advice for other military personnel on the proper conduct of massive air war. He justifies his targeting of civilian infrastructure by arguing that "laws of warfare were, strictly speaking, not fully applicable." Echoing generals throughout history, he criticizes the limitations that were put on NATO commanders by politicians. c. Book News Inc.
Include Index, Maps and Colour Illustration
Keywords: Bosnia and Herzegovina -- Kosovo (Republic) -- Yugoslav War (1991-1995)